Knowledge and attitudes of women regarding mother-to-child transmission of HIV infection in the Ehlanzeni District, Mpumalanga Province, South Africa - Sechabe, Ednah Virginia (My University, 2011)
HIV/AIDS is one of the major challenges facing South Africa today. Over 5.5 million people are infected with HIV and the majority of these infections are in the reproductive age group. Since the start of the epidemic, over 12.2 million women worldwide have been infected with HIV (WHO, 2000:10). The risk of women contracting HIV is rising globally. HIV seems to be a major cause of infant mortality. It is estimated that approximately 55% of women in South Africa are HIV-positive (National Department of Health, 2007:7). It is, therefore, important that knowledge and attitudes of women regarding mother-to-child transmission (MTCT) of HIV infection are explored to reduce the high infant mortality rate and the incidence of MTCT of HIV infections, and to develop preventive programmes on HIV and AIDS. In view of these considerations, the objectives of this study were to explore and describe the knowledge and attitudes of women with regard to MTCT of HIV infection and to provide guidelines for the prevention of MTCT of HIV infection. The study was conducted in the rural area of the Ehlanzeni District in the Mpumalanga Province, South Africa at Bourke’s Luck and Elandsfontein clinics. An explorative, descriptive, qualitative research design that is contextual in nature was used. The population consisted of all pregnant women and those in pueperium between 25-40 years of age. Non-probability purposive sampling was used. Participants were selected according to inclusion criteria. Data were collected using semi-structured interviews. The research findings revealed that some participants had knowledge and understanding regarding MTCT of HIV infection while others lacked knowledge and understanding which could impact on MTCT of HIV infection.
Thesis (M. Cur.) --University of Limpopo, 2011.
Keywords: HIV infections; AIDS disease; HIV infections -- South Africa; AIDS (Disease) -- South Africa; HIV (Viruses) -- Transmission; HIV Infections --Transmission -- South Africa